Estimation of non-high-density lipoprotein cholesterol and its correlation as a surrogate measure of apolipoprotein B in patients with metabolic syndrome - K G Prakash; B Sumana; Abhiman B Shetty (Wolters Kluwer Medknow Publications, 2020)
Background: The primary target of therapy for dyslipidemia according to the present lipid guidelines is low-density lipoprotein cholesterol (LDL-C). Its main drawback is it is a derived value and erroneous values may be obtained if triglyceride values are high. Hence, direct measurement of apolipoprotein B (Apo-B), which is present in all atherogenic particles (very-LDL, intermediate-density lipoprotein, and LDL) would be ideal and is a superior indicator of cardiovascular risk. However, current limitations of Apo-B estimation are lack of standardization and lack of technical expertise and cost factor. To overcome these limitations, there is a need to test a particular lipid value from the standard lipid test, which can be used as a surrogate measure of Apo-B. As non-high-density lipoprotein cholesterol (HDL-C) is a measure of the cholesterol content of all Apo-B-containing lipoproteins, it may represent a simple and inexpensive surrogate to Apo-B in select patient subgroups. Hence, this study was undertaken to estimate non-HDL-C and LDL-C from the standard lipid test and also measure Apo-B levels in patients with metabolic syndrome using appropriate statistical methods, correlation and concordance between non-HDL-C versus Apo-B and LDL-C versus Apo-B were analyzed. Methodology: This was a cross-sectional study carried out in Bangalore on 135 patients of metabolic syndrome fulfilling the International Diabetes Federation criteria, from January 2019 to March 2019. Detailed history and examination was undertaken. Fasting blood glucose, Apo-B-100, and lipid profile were obtained in the fasting state venous blood sample. Results: A significant positive correlation was noted between non-HDL-C levels and Apo-B values with a correlation coefficient of 0.883 and area under the curve (AUC) of 0.972. In contrast, the correlation between LDL-C and Apo-B-100 showed a correlation coefficient of 0.815 and AUC of 0.949. Similarly, the concordance/discordance analysis of the same parameters showed concordance across the range of corresponding non-HDL-C and Apo-B quintiles except in the middle quintile where the values were discordant. Concordance was >50% across 80% of the range of values between LDL-C and non-HDL-C. Conclusion: This study showed that there is a good correlation between non-HDL-C levels and Apo-B values with less discordance. Hence, non-HDL-C can be used as a simple and cost-effective alternative (surrogate) to Apo-B estimation.